Late Quaternary palaeoenvironmental reconstruction from Lake Ohrid - Lacey, Jack H. (2016)
Lake Ohrid is a large, deep, ancient lake located on the Balkan Peninsula and has an extraordinary degree of endemic biodiversity. A deep drilling campaign was carried out in 2013 as part of the Scientific Collaboration on Past Speciation Conditions in Lake Ohrid (SCOPSCO) project to better understand the influence of climate and environmental change on evolutionary patterns and endemism. Initial results from a 569 m sediment succession drilled in the centre of the basin indicate continuous lacustrine conditions over the past ca. 1.2 Ma. This thesis presents new stable isotope data from carbonate within the upper 248 m of the composite profile, covering the last ca. 640 ka at a millennial-scale resolution (≈ 0.5 ka). Isotope data are used to provide a long-term palaeoenvironmental reconstruction, which is supported by a quantitative model of modern lake water isotope composition and a detailed multi-proxy investigation of climate evolution since the last glacial period.